Multiple cardiovascular risk factor care in 55 low- and middle-income countries: A cross-sectional analysis of nationally-representative, individual-level data from 280,783 adults. - Alpha Oumar Diallo; Maja E Marcus; David Flood; Michaela Theilmann; Nicholas E Rahim; Alan Kinlaw; Nora Franceschini; Til Stürmer; Dessie V Tien; Mohsen Abbasi-Kangevari; Kokou Agoudavi; Glennis Andall-Brereton; et al. (Public Library of Science (PLoS), 2024)
The prevalence of multiple age-related cardiovascular disease (CVD) risk factors is high among individuals living in low- and middle-income countries. We described receipt of healthcare services for and management of hypertension and diabetes among individuals living with these conditions using individual-level data from 55 nationally representative population-based surveys (2009-2019) with measured blood pressure (BP) and diabetes biomarker. We restricted our analysis to non-pregnant individuals aged 40-69 years and defined three mutually exclusive groups (i.e., hypertension only, diabetes only, and both hypertension-diabetes) to compare individuals living with concurrent hypertension and diabetes to individuals with each condition separately. We included 90,086 individuals who lived with hypertension only, 11,975 with diabetes only, and 16,228 with hypertension-diabetes. We estimated the percentage of individuals who were aware of their diagnosis, used pharmacological therapy, or achieved appropriate hypertension and diabetes management. A greater percentage of individuals with hypertension-diabetes were fully diagnosed (64.1% [95% CI: 61.8-66.4]) than those with hypertension only (47.4% [45.3-49.6]) or diabetes only (46.7% [44.1-49.2]). Among the hypertension-diabetes group, pharmacological treatment was higher for individual conditions (38.3% [95% CI: 34.8-41.8] using antihypertensive and 42.3% [95% CI: 39.4-45.2] using glucose-lowering medications) than for both conditions jointly (24.6% [95% CI: 22.1-27.2]).The percentage of individuals achieving appropriate management was highest in the hypertension group (17.6% [16.4-18.8]), followed by diabetes (13.3% [10.7-15.8]) and hypertension-diabetes (6.6% [5.4-7.8]) groups. Although health systems in LMICs are reaching a larger share of individuals living with both hypertension and diabetes than those living with just one of these conditions, only seven percent achieved both BP and blood glucose treatment targets. Implementation of cost-effective population-level interventions that shift clinical care paradigm from disease-specific to comprehensive CVD care are urgently needed for all three groups, especially for those with multiple CVD risk factors.